(untitled) (Comprehensive Journal of Science, 2025)
Libyan seaports face increasing challenges within a dynamic business environment characterized by regional and global competition. This necessitates the adoption of innovative strategies to enhance operational performance and institutional excellence. This study aims to analyze the strategic role of information technology in enabling Libyan ports to achieve competitive advantages by improving operational efficiency , facilitating information flow , and strengthening decision-making capabilities. This research utilizes a descriptive -analytical methodology, supported by both quantitative and qualitative collection tools, including structured meeting and some interviews with professional and experts in the maritime transport sector. The study was applied to a selected group of Libyan ports chosen based on their exposure to economic and technological shifts. It evaluates the extent to which management information system, digital tracking technologies ,and integrated logistics to enhancing competitive capabilities. Findings indicate that effective utilization of information technology helps reduce procedural delays, improve services quality, and increase transparency -positively impacting the positioning of Libyan ports within global supply chains .The study concludes with recommendations to adopt sustainable digital policies , upgrade technical infrastructure, and invest in qualified human capital to ensure continued competitive excellence in this vital sector.